Morphological characterization of Mahabubnagar goats - EKAMBARAM*, B; GUPTA, B R; PRAKASH, M G; SUDHAKER, K; REDDY, V R (The Indian Journal of Animal Sciences, 2011)
In a field study covering 172 farmers spread over 56 villages in 20 mandals, data were collected on the morphological characteristics of 1590 Mahabubnagar goats. The predominant coat colour was bicolour (63.5%) followed by single colour (25%) and multicolour (11.5%) on overall basis. The bicolour coat pattern consisted of mainly black and white (30.88%) followed by brown and white (22.14%) and black and brown (10.38%). Pendulous ears were predominant (91.57%) followed by erect (4.59%) and horizontal ears (3.84%). Majority of the goats (85.97%) had beard while wattles were present in only 34.34% of goats. Straight and curved horns were observed in 96.04% of animals in both sexes. Horn size was mostly medium (63.46%) followed by large size (10.81%) while 10.81% of animals had large horns oriented backward and backward and downward.